Exogenous Melatonin Regulates Puberty and the Hypothalamic GnRH-GnIH System in Female Mice - Zixuan Chen; Lina Si; Weihan Shu; Xin Zhang; Chenyang Wei; Meng Wei; Luyang Cheng; Zhihong Chen; Yuebing Qiao; Songhe Yang (Brain Sciences, 2022)
In recent years, the age of children entering puberty is getting lower and the incidence of central precocious puberty is increasing. It is known that melatonin plays an increasingly important role in regulating animal reproduction, but the specific role and mechanism of melatonin in regulating the initiation of puberty remain unclear. The purpose of the current study was to investigate the effect of subcutaneous melatonin injection on pubertal development in female mice and its mechanism of action. Female mice that were 22 days old received 1 mg/kg doses of melatonin subcutaneously every day for 10, 15 and 20 days. The vaginal opening was checked daily. Hematoxylin and eosin (HE) stain was used to determine the growth of the uterus and ovaries. Enzyme-linked immunosorbent assay (ELISA) was used to determine the levels of follicle-stimulating hormone (FSH), gonadotropin-inhibiting hormone (GnIH), and gonadotropin-releasing hormone (GnRH) in serum. By using RT-PCR and Western blotting, the mRNA and protein expression of the hypothalamus GnRH, GnIH, Kisspeptin (Kp), Proopiomelanocortin (POMC), Neuropeptide Y (NPY), as well as G protein-coupled receptor 147 (GPR147) were identified. The findings demonstrated that melatonin could suppress ovarian follicle and uterine wall growth as well as delay vaginal opening, decrease serum levels of GnRH and FSH and increase levels of GnIH. Melatonin increased GnIH and GPR147 expression in the hypothalamus in comparison to the saline group, while decreasing the expression of GnRH, Kisspeptin, POMC, and NPY. In conclusion, exogenous melatonin can inhibit the onset of puberty in female mice by modulating the expression of hypothalamic GnRH, GnIH, Kisspeptin, POMC and NPY neurons and suppressing the hypothalamic–pituitary–gonadal axis.